Stenopterobia cataractarum sp. nov. (Bacillariophyta), a new benthic diatom from a waterfall in Zambia, Africa - Cocquyt, Christine; Taylor, Jonathan Charles; Wetzel, Carlos (Phytotaxa, 2014)
Rivers, streams and associated habitats have been sampled for diatoms in the relatively understudied Congo and Zambezi sister basins. The primary purpose of the sampling effort was to collect samples for biological monitoring purposes and the establishment of a diatom-based monitoring programme. However, a large number of possibly endemic and novel taxa have been encountered in this region making the application of diatom-based indices at a species level difficult. In this paper we describe a new species of Stenopterobia from the Ntumbachushi Falls in the Luapula Province of Zambia. This taxon is closely related to Stenopterobia delicatissima but chiefly differentiated by a lower number of striae, a well-defined unornamented lanceolate axial area and shortened ribs which do not fuse with the fenestrae. This taxon also shows some similarity to Stenopterobia delicatissima var. ghanaensis but the valves are consistently narrower.